The effect of prestimulus low-frequency neural oscillations on the temporal perception of audiovisual speech - Jiang, Zeliang; An, Xingwei; Liu, Shuang; Wang, Lu; Yin, Erwei; Yan, Ye; Ming, Dong (Frontiers in Neuroscience, 2023)
Perceptual integration and segregation are modulated by the phase of ongoing neural oscillation whose frequency period is broader than the size of temporal binding window (TBW). Studies have shown that the abstract beep-flash stimuli with about 100 ms TBW were modulated by the alpha band phase. Therefore, we hypothesize that the temporal perception of speech with about hundreds of milliseconds of TBW might be affected by the delta-theta phase. Thus, we conducted a speech-stimuli-based audiovisual simultaneity judgment (SJ) experiment. Twenty human participants (12 females) attended this study, recording 62 channels of EEG. Behavioral results showed that the visual leading TBWs are broader than the auditory leading ones (273.37 ± 24.24 ms vs 198.05 ± 19.28 ms). We used Phase Opposition Sum (POS) to quantify the differences in mean phase angles and phase concentrations between synchronous and asynchronous responses. The POS results indicated that the delta-theta phase was significantly different between synchronous and asynchronous responses in the A50V condition. However, in the V50A condition, we only found the delta band effect. We did not find a consistency of phases over subjects for both perceptual responses by the post hoc Rayleigh test (all ps＞0.05), but V-test showed the phase difference between synchronous and asynchronous responses had a significant phase opposition(all ps ＜ 0.05). These results indicate that the speech temporal perception depends on the alignment of stimulus onset with an optimal phase of the neural oscillation whose frequency period might be broader than the size of TBW. The role of the oscillatory phase might be encoding the temporal information which varies across subjects rather than neuronal excitability.